Long-term results of outpatient rehabilitation after coronary artery bypass graft surgery - T. N. Zvereva; I. V. Samus; A. A. Pronina; I. N. Lyapina (Фундаментальная и клиническая медицина)
Aim. To assess the impact of adherence to various outpatient rehabilitation programs during the first three months after coronary artery bypass grafting (CABG) on the development of cardiovascular events over four years of follow-up.Materials and Methods. The study evaluated the influence of adherence to outpatient cardiac rehabilitation programs on the incidence of cardiovascular events in patients following open coronary artery revascularization surgery. Adherence to cardiac rehabilitation was assessed over a threemonth period, and the observation period for cardiovascular events extended to four years from the time of the surgery.Results. During the first year of observation, we did not find significant differences in the effectiveness and safety of outpatient cardiac rehabilitation programs. However, we revealed statistically significant differences in the patient adherence to physical training. Over the four-year observation period, a higher number of cardiovascular events were recorded in the group of patients who were non-adherent to physical training. Statistically significant differences were observed with regards to the incidence of myocardial infarction and cardiovascular death.Conclusion. Adherence to recommendations following open revascularization procedures is crucial for the prognosis of myocardial infarction and cardiovascular death. Modern methods of providing medical care in the outpatient phase of cardiac rehabilitation enable patients to engage in effective and safe physical training comparable to those conducted in specialized cardiac rehabilitation facilities under the direct supervision of medical personnel.